Performance, carcass yield, and meat quality of free-range broilers fed wet grain corn silage - Saldanha, E. S. P. B.; Mendes, Ariel Antonio [UNESP]; Pizzolante, C. C.; Takahashi, S. E. [UNESP]; Komiyama, C. M. [UNESP]; Garcia, R. G.; Balog Neto, A. [UNESP]; Paz, Ibiara Correia de Lima Almeida [UNESP]; Garcia, Edivaldo Antonio [UNESP]; Dalanezi, J. A. [UNESP]; Quinteiro, R. R. [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2006)
This study aimed at evaluating the effect of total replacement of dry corn by wet grain corn silage (WGCS) in the feed of label broilers older than 28 days of age on performance, mortality, carcass, parts, breast meat and thighs meat yields, and meat quality. A mixed-sex flock of 448 ISA S 757-N (naked-neck ISA JA Label) day-old chicks was randomly distributed in to randomized block experimental design with four treatments (T1 - with no WGCS; T2 - WGCS between 28 and 83 days; T3 - WGCS between 42 and 83 days; and T4 - WGCS between 63 and 83 days) and four replicates of 28 birds each. Birds were raised under the same management and feeding conditions until 28 days of age, when they started to have free access to paddock with pasture (at least 3m²/bird) and to be fed the experimental diets. Feed and water were offered ad libitum throughout the rearing period, which was divided in three stages: starter (1 to 28 days), grower (29 to 63 days), and finisher (64 to 83 days) according to the feeding schedule. During the short periods of WGCS use (group T2 during grower stage and T4 during the finisher stage), performance and mortality results were similar as to those of the control group (T1). At the end of the experiment, it was observed that the extended use of WGCS (T2 and T3) determined a negative effect on feed conversion ratio. However, the best results of breast meat yield were observed with birds fed WGCS since 28 days (T2). It was concluded that WGCS can replace dry corn grain for short periods during the grower and finisher stages with no impairment of meat quality and yield in slow growth broilers.
Keywords: Feeding; label chickens; production; rearing system